A WFS1 Haplotype Consisting of the Minor Alleles of rs752854, rs10010131, and rs734312 Shows a Protective Role Against Type 2 Diabetes in Russian Patients (The Review of Diabetic Studies, 2023)
BACKGROUND: Rare variants of the WFS1 gene encoding wolframin cause Wolfram syndrome, a monogenic disease associated with diabetes insipidus, diabetes mellitus, optic atrophy, and deafness. In contrast, common variants of WFS1 showed association with type 2 diabetes (T2D) in numerous Caucasian populations. AIM: In this study, we tested whether the markers rs752854, rs10010131, and rs734312, located in the WFS1 gene, are related to the development of T2D in a Russian population. METHODS: The polymorphic markers were genotyped in Russian diabetic (n = 1,112) and non-diabetic (n = 1,097) patients using a Taqman allele discrimination assay. The correlation between the carriage of disease-associated WFS1 variants and the patients’ clinical and metabolic characteristics was studied using ANOVA and ANCOVA. Adjustment for confounding variables such as gender, age, body mass index, obesity, HbA1c, and hypertension was made. RESULTS: Haplotype GAG, consisting of the minor alleles of rs752854, rs10010131, and rs734312, respectively, showed association with decreased risk of T2D (OR = 0.44, 95% CI = 0.32-0.61, p = 4.3 x 10-7). Compared to other WFS1 variants, non-diabetic individuals homozygous for GAG/CAG had significantly increased fasting insulin (padjusted = 0.047) and homeostasis model assessment of β-cell function (HOMA-β) index (padjusted = 0.006). Diabetic patients homozygous for GAG/GAG showed significantly elevated levels of 2-h insulin (padjusted = 0.029) and HOMA-β = 0.011. CONCLUSIONS: Diseaseassociated variants of WFS1 contribute to the pathogenesis of T2D through impaired insulin response to glucose stimulation and altered β-cell function.